Merzbau: the interpretation of the world as a living form without first causes - Pousada, Pedro (PORTO ARTE: Revista de Artes Visuais, 2017)
This article is gives further thought to the article “Merzbau, the grave of the logocentric self: He who screams becomes the space”, published in the Porto Arte journal, issue 34, 2015, presenting considerations on the Merzbau of Hanover as a “para-architectural” experience and as a doctrine of environmental comfort, linked to intense sensation and mnemonic relaxation.